Marriage Contract and Legal Results Against Women - Salle; Asriati; Labatjo, Ridwan; Alfian; Djanggih, Hardianto (International Journal of Psychosocial Rehabilitation, 2020)
In the aspect of Islamic law, mut’ah marriage was permitted by the Messenger of Allāh W during the war period. However, this acquisition has been abolished, or the law of marriage mut’ah is forbidden and will be sinful for those who do it. In the aspect of national law, contract marriage is considered a legal flaw because it contradicts Article 2, paragraph (1), of Law Number 1 of 1974 concerning Marriage; Article 1337 and Article 1332 of the Civil Code; the principle of marriage; and the purpose of marriage. Based on these provisions, a legal marriage is carried out in accordance with religious teachings and beliefs and does not conflict with moral values. Registered or registered marriages in accordance with applicable laws and regulations will be protected by the state. The practice of contract marriage actually positions the position of women as very weak in the eyes of the law because the marriage is considered never to have taken place, so that the wife is not considered a legal wife, the wife is not entitled to a living and inheritance from her husband if he dies, and the wife is not entitled to Gono Gini’s assets if it occurs farewell, because legally, the marriage contract is considered to have never happened.